PENYUSUNAN DRAFT STANDARD OPERATING PROCEDURE (SOP) PEMBUATAN GULA MERAH KELAPA (STUDI KASUS DI PENGRAJIN GULA MERAH KELAPA DESA PURWOREJO KEC. NEGERI KATON KAB. PESAWARAN) - Yusuf Muchaymien; Azhari Rangga; Fibra Nuraini (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
The objective of this research was to improve coconut brown sugar quality produced by coconut sugar farmers in Purworejo Village Negeri Katon , District in Pesawaran Regency by composing SOP draft. This research was conducted through five stages: (1) field observations to collect the data form coconut sugar farmers and coconut sugar producers using  interviews and questionnaires; (2) determination of critical point and optimal conditions of processing stage; (3) composing of SOP draft; (4) testing SOP draft, and (5) observations to products after SOP draft implementations on particular coconut brown  sugar producers. The data were analyzed descriptively. The results showed that the moisture contents of coconut sugar before and after SOP draft implementations were 9.47% and 7.12% respectively. This  indicates that coconut sugar product after SOP draft implementation contained lower moisture content compared to those without SOP draft implementation, and the product had fulfilled SNI requirement for moisture content.  The implementation of SOP draft had also caused decreased in ash content from  2.22% to 5,7% in those without SOP draft and it was close to SNI quality requirements (maximum 2.0%).  The average  content of reducing sugar of the product implementing SOP draft was 3.39% compared to those without SOP draft implementation (5.46%), and it met the SNI quality requirement (maximum 10%). Organoleptically, coconut brown  sugar produced after SOP draft implementation had less bitter taste, harder texture and brown yellowish or brighter color , whereas the ones without SOP draft implementation  had darker color.  The overall acceptance of  coconut sugar products after SOP draft implementation was more desirable  compared to those of without SOP draft implementation. Keywords         : coconut sugar,  Pesawaran, SOP draft.